EFEKTIVITAS YOGA DALAM MENGATASI KECEMASAN IBU HAMIL DAN DEPRESI POSTPARTUM: SYSTEMATIC REVIEW: EFFECTIVENESS YOGA FOR ANXIETY DURING PRENATAL AND POSTPARTUM DEPRESSION: SYSTEMATIC REVIEW - Tasa Nabilla; Endang Dwiyanti (Journal of Community Mental Health and Public Policy, 2022)
ABSTRACT Yoga is often used as a stress management therapy that involves the human body as a whole, and is more often chosen as a therapy for anxiety or depression. Methods: Research design systematic review. This study uses secondary data in the form of data from the results of previous studies. The timing of the selected test results is between 2015 and 2022. Research data is sought from database a systematic and comprehensive, Springer Link, Google Scholar, Chocrane Library. The population in this study were pregnant women and postpartum women, the intervention was yoga practice, comparison in this study was without yoga practice and outcomes obtained were a decrease in anxiety in pregnant women and depression during postpartum. Results: The primary studies taken were 9 journals. Critical Appraisal in RCT studies using CEBM (Center for Evidence-Based Medicine) and in quasi-experimental design studies using The JBI Critical Appraisal. In 9 primary studies that were analyzed using critical appraisal, scores were above 50%. In 9 primary studies analyzed, the outcome of yoga practice was to reduce anxiety during pregnancy and depression during postpartum. Conclusion: There is an effect after yoga practice on anxiety during pregnancy and depression during postpartum. ABSTRAK Yoga sering digunakan sebagai terapi manajemen stres yang melibatkan anggota tubuh manusia secara keseluruhan, dan lebih sering dipilih sebagai terapi untuk kecemasan atau depresi. Metode: Desain penelitian systematic review. Penelitian ini menggunakan data sekunder berupa data dari hasil penelitian sebelumnya. Waktu dari hasil uji yang dipilih antara tahun 2015 sampai 2022. Data penelitian dicari dari database yang sistematis dan komprehensif diantaranya: PubMed, Science Direct, Springer Link, Google Scholar, Chocrane Library. Populasi dalam penelitian ini adalah Ibu hamil dan Ibu postpartum, intervensinya adalah latihan yoga, comparison dalam penelitian ini adalah tanpa latihan yoga dan outcome yang didapatkan penurunan kecemasan pada ibu hamil dan depresi selama postpartum. Hasil: studi primer yang diambil sebanyak 9 jurnal. Critical Appraisal pada studi RCT menggunakan CEBM (Center for Evidance- Based Medicine) dan pada studi desain quasi eksperimen menggunakan The JBI Critical Appraisal. Pada 9 studi primer yang dianalisis menggunakan critical appraisal didapatkan skor diatas 50%. Pada 9 studi primer yang dianalisis didapatkan outcome latihan yoga dapat menurunkan kecemasan selama hamil dan depresi saat postpartum. Kesimpulan: Terdapat pengaruh setalah latihan yoga terhadap kecemasan selama kehamilan dan depresi pada saat postpartum.